Size of anal squamous cell carcinomas at diagnosis: a retrospective case series. (November 2013) - Read, TRH; Huson, KL; Millar, JL; Haydon, A; Porter, IWT; Grulich, AE; Hocking, JS; Chen, MY; Bradshaw, CS; Fairley, CK
Anal squamous cell carcinoma is more common in HIV-positive homosexual men than in the general population and prognosis worsens with increasing tumour size. To identify opportunities for earlier diagnosis, we aimed to determine size and visibility of anal squamous cell carcinoma at diagnosis. We conducted a retrospective review of medical records between 1992 and 2010 from one hospital radiotherapy centre, a major centre for HIV care, in Melbourne, Australia. Of 128 cases of anal squamous cell carcinoma, 24 (19%) were in HIV-positive men. At diagnosis, half (52%) of the tumours were externally visible and mean estimated tumour size was 36 mm (29 mm in HIV-positive and 38 mm in HIV-negative patients; p  = 0.04) and 114/121 (94%) tumours were 1 cm or larger. The most frequent symptoms were bleeding (43%) and pain (36%) and mean duration of symptoms was 22 weeks. This suggests most anal squamous cell carcinoma were visible or palpable for some time before diagnosis, meaning that screening high-risk groups by anal inspection and palpation is plausible.